Evolutionary Understanding of the Human Mind and Learning -- in Accordance with Transactional Naturalism and Methodological Relationalism - Kivinen Osmo; Piiroinen Tero (Elsevier B. V., 2022)
The approach to the evolution of human culture and mind suggested in this article represents transactional naturalism combined with methodological relationalism. In transactions, the organism changes the environment and vice versa. Transactional naturalism conceptualizes the human mind and awareness in a relational vein, as coevolving with the human socio-cultural niche, much like enactive and extensive theories of mind. The approach is in stark contrast with gene-centered and psychologizing nativist naturalism which views consciousness and language faculty as innate. The origin of the concept of transaction is in classical American pragmatism, in particular in Dewey’s theory of action according to which one can learn only in action and in action one cannot but learn. Apprentice learning setup, emphasized by Kim Sterelny in particular, has been pivotal for the development of human community since the Pleistocene era. Coevolving with social institutions, human learning has played an exceptional role in cultural innovations when useful knowing-how and skilled habits have been transferred from generation to generation. Therefore humans deserve the epithet Homo discens, learning man.